(untitled) (Journal of Science-Innovative Research in Uzbekistan, 2023)
This comprehensive overview explores the vital concept of oral hygiene, emphasizing its critical role in maintaining optimal dental health and preventing oral diseases. Covering fundamental practices such as brushing, flossing, and tongue cleaning, the discussion extends to the prevention of common dental issues, the impact of diet on oral health, and the significance of regular dental check ups. The article highlights the personalized nature of oral care, considering individual needs and special considerations. Moreover, it underscores the systemic connections between oral health and overall well-being, emphasizing the role of education in promoting public awareness and dental health literacy